(untitled) (Journal of Engineering, 2017)
This work aimed to design, construct and operate a new laboratory scale water filtration system. This system was used to examine the efficiency of two ceramic filter discs as a medium for water filtration. These filters were made from two different ceramic mixtures of local red clay, sawdust, and water. The filtration system was designed with two rotating interfered modules of these filters. Rotating these modules generates shear force between water and the surfaces of filter discs of the filtration modules that works to reduce thickness of layer of rejected materials on the filters surfaces. Each module consists of seven filtration units and each unit consists of two ceramic filter discs. The average measured hydraulic conductivity of the first module was 13.7mm/day and that for the second module was 50mm/day. Results showed that the water filtration system can be operated continuously with a constant flow rate and the filtration process was controlled by a skin thin layer of rejected materials. The ceramic water filters of both filtration modules have high removal efficiency of total suspended solids up to 100% and of turbidity up to 99.94%.